AI-Enabled Smart Drug Delivery Systems Inspired by Natural Bioactive Polysaccharides: From Microbiome Modulation to Personalized Healthcare Applications - Lars Hayes; Niklas Perry (International Journal of Clinical and Translational Medicine, 2026)
The convergence of artificial intelligence, materials science, and systems engineering is opening unprecedented opportunities for smart drug delivery platforms that leverage the unique properties of natural bioactive polysaccharides. These biopolymers offer inherent biocompatibility, programmable degradation, mucoadhesion, and prebiotic activity, making them ideal scaffolds for targeting the gut microbiome while simultaneously delivering therapeutic agents. However, translating such multifunctional carriers into clinically viable personalized interventions demands a comprehensive system-level rethinking of design, deployment, and governance. This paper presents an interdisciplinary analysis of AI-enabled smart drug delivery systems inspired by polysaccharide chemistry, with a focus on the interplay between carrier architecture, microbiome modulation, and patient-specific data streams. We examine how machine learning can guide the discovery and optimization of polysaccharide conjugates, predict host–microbiome–drug interactions, and orchestrate closed-loop sensing and release. The discussion extends to infrastructure requirements for integrating wearable sensors, edge computing, and cloud-based learning for real-time adaptation. We critically assess structural trade-offs involving latency, data sovereignty, model interpretability, and regulatory alignment. Through a systems lens, we address fairness, sustainability of polysaccharide sourcing, and the policy implications of deploying autonomous drug delivery devices across diverse populations. Case illustrations are drawn from emerging research on bioactive polysaccharides that influence metabolic and microbial phenotypes. The paper argues that realizing the full potential of such integrated platforms requires not only advances in AI and biomaterials but also robust governance frameworks that balance innovation with equity and safety, ultimately enabling truly personalized, microbiome-aware healthcare.